Persona Non Grata Dalam Praktek Negara Rusia dan Ukraina Beserta Implikasi Hukumnya - Yulifia Serafina Refra; Irma Halimah Hanafi; Veriana Josepha Batseba Rehatta (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: This statement of persona non grata has become a habit in diplomatic relations and is often misused by many countries. As happened between the receiving country (Russia) and the sending country (Ukraine) which expelled each other's diplomats, causing legal implications for both countries.Purposes of the Research: The purpose of this research is to find out how the practice of the receiving country in implementing persona non grata towards the sending country and to find out the legal consequences arising from the actions of the sending country and the receiving country based on the 1961 Vienna Convention. Methods of the Research: The research method in this study is a normative legal research, using a law approach, a case approach and a conceptual approach. Sources of research data include sources of library studies. Processing and analysis of legal materials used in writing is using processing and computerization methods so that legal materials can be analyzed completely and comprehensively.Results of the Research: Based on the results of research on the practice of giving persona non grata by Russia to Ukrainian diplomats on charges of espionage or espionage, the allegations were not justified by Ukraine. However, what the two countries did was contrary to the 1961 Vienna Convention because there was a need for a diplomatic representative for relations between the two countries. After expelling diplomats, this problem continued when Russia invaded Ukraine, causing war between the two parties. For this reason, in the international legal dispute settlement stage, it has been recommended that the two countries settle disputes peacefully in accordance with what has been regulated in Article 33 of the United Nations Charter.